Closed-Loop Adaptive High-Starting Torque Scalar Control Scheme for Induction Motor Variable Speed Drives - Travieso-Torres, J; Travieso-Torres, J; Diaz-Diaz, M (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
This article proposes a closed-loop (CL) high-starting torque (HST) scalar control scheme (SCS) for induction motors (IM). It endows the recently proposed HST-SCS with high-output torque capability beyond starting after using an outer speed control loop feeding an inner current control loop with adaptive controllers. Presenting a cascade normalized adaptive passivity-based controller (N-APBC) for nonlinear systems encompassing the IM allows obtaining this result. It extends the normalized adaptive controller for the cascade case. As a result, it keeps the HST-SCS simple control scheme without needing variable observers or parameter estimators and employing tuning information only from the motor nameplate and datasheet. Test bench experiments with a 10 HP motor validate the proposal’s effectiveness. Comparative experimental results show that the CL HST-SCS has a required stator phase voltage lower than HST-SCS. The CL HST-SCS applies the adaptive starting voltage curve for a more extended time than HST-SCS, from the start to 1.9 s versus 1.2 s, respectively. Hence, CL HST-SCS assures HST not only for starting but almost up to 600 rpm, resulting in a smoother transient behavior than HST-SCS under this speed. © 2022 by the authors. Licensee MDPI, Basel, Switzerland.